Determinants of health seeking behaviours for malaria treatment in Cameroon - Nounouce, Ngako Pamen Joelle; Zakariaou, Njoumemi; Yollande, Tankeu; Marie-José, Essi; Wilfred, Mbacham F.; Roger, Somo M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Household health-seeking behaviour for malaria treatment is an important policy concern in malaria-endemic African countries. This paper aims to shed light on the determinants of household’s health-seeking behaviour for malaria treatment in Cameroon. Methods: The cross-sectional study used secondary data from the fourth Cameroonian household consumption survey conducted by the National Institute of Statistics. A stratified, 2-stage sampling was implemented with a sample of 918 households which sought malaria treatment from different alternatives providers. The multinomial probit model was used to estimate the probability based on socio-demographic and economics determinants for a household to choose between different types of providers of malaria treatment. Results: The findings of this study indicate that, the alternative providers for malaria treatment were: public health facilities (61.1%), private health facilities (8.5%), traditional healers (1.4%), pharmacies (4.6%), informal vendor (18%), other types of recourse (6.4%). The decision to choose the provider for malaria treatment depends on factors such as household head, region, level of education, religion, area of residence, socio-professional category, and gender. The level of education appears to be an important determinant of a household’s seeking behaviour. Those with higher education are more likely to seek care at formal health facilities. Conclusions: Health policy-makers need to strive to improve the socio-demographic and economic conditions and sensitize households on the appropriate alternative ways to ensure the universal access to diagnosis and effective treatment of malaria in line with the global strategies recommended by WHO to achieve malaria elimination by 2030.